SAT0083 Does Specific Joint Involvement in Rheumatoid Arthritis Patients PREDICT Patient Reported Outcomes? Implications for Clinical Practice. (10th June 2014) - Arendse, R.; Bensen, W.G.; Chow, A.; Rodrigues, J.; Dixit, S.; Sholter, D.; Baer, P.; Baker, M.; Choquette, D.; Fortin, I.; Jovaisas, A.; Rampakakis, E.; et al.
Abstract : Background: Assessment of functional (dis)ability in rheumatoid arthritis (RA) is subject to patient judgment when appraising their ability to do daily activities. Objectives: The aim of this analysis was to describe the impact of specific joint involvement on patient reported outcomes (PROs) - functional activity, pain and patient global assessment of disease activity (PtGA) - and to identify joints most resistant to treatment over time. Methods: Biologic Treatment Registry Across Canada (BioTRAC) is an ongoing, prospective, registry of patients initiating treatment for RA, AS, or PsA with infliximab or golimumab as first biologics or after having been treated with a biologic for less than six months. In this analysis, data were included from RA patients treated with infliximab between 2002 and 2012 or with golimumab between 2010 and 2012. Based on joint involvement seven groups were created: shoulder(s), elbow(s), metacarpophalangeal (MCP), wrist(s), proximal interphalangeal (PIP), knee(s), and thumb(s). The impact of specific joints on patient outcomes was assessed with the independent-samples t-test. Linear regression was used in order to produce adjusted estimates. Results: A total of 935 RA patients with 4, 854 assessments were included. Swelling, tenderness, and swelling and/or tenderness in all joint groups were associated with significantly (P<0.001) higher HAQ-DI, PtGA, and pain. Upon adjusting for age, gender and the total number of swollen (SJC28) and tender (TJC28) joints, swelling in all joint groups but the thumb(s) had a significant impact on PtGA, pain and HAQ. Similarly, tenderness in all joints but PIP had a significant impact on these parameters. Overall, swelling and/or tenderness at specific joints - shoulders, wrists, knees and elbows - had the greatest impact on HAQ-DI, PtGA, and pain (P<0.001). Swollen and/or tender PIP(s) did not have a significant effect on any PRO. At baseline, the MCP joint(s) and the wrist(s) were the most commonly swollen (86.4% and 67.9% of patients, respectively) or tender (82.9% and 73.1%, respectively) joints. Upon 12 months of treatment, the MCP joints were the joints most resistant to treatment, still remaining affected. Conclusions: Significant variability in PROs exists based on the presence of swelling and/or tenderness in specific joint groups. Swelling/tenderness of shoulders, wrists, knees and elbows were the main drivers of HAQ-DI, PtGA and pain. The results have important implications for the achievement of disease remission and suggest that the joint type in addition to the number of affected joints has unique impact on PROs. Disclosure of Interest: R. Arendse: None declared, W. Bensen: None declared, A. Chow: None declared, J. Rodrigues: None declared, S. Dixit: None declared, D. Sholter: None declared, P. Baer: None declared, M. Baker: None declared, D. Choquette: None declared, I. Fortin: None declared, A. Jovaisas: None declared, E. Rampakakis: None declared, J. Sampalis: None declared, F. Nantel Employee of: Janssen Inc Canada, S. Otawa Employee of: Janssen Inc Canada, M. Shawi Employee of: Janssen Inc Canada, A. Lehman Employee of: Janssen Inc Canada DOI: 10.1136/annrheumdis-2014-eular.5185